Representation as an Important Institution of Civil Law - Zogiani Ermonda (SEEU Review)
Representation is a fundamental institution within civil law, playing a crucial role in the resolution of legal affairs. Subjects of law during the establishment of legal affairs or undertaking various procedural actions in civil litigation procedures may engage representatives who act on behalf and for the benefit of their interests. This paper explores the significance of representation as a legal mechanism including its impact on the efficacy of legal proceedings and the protection of parties' interests.